Pelatihan Aviation Security Awareness Bagi Personel Penerbangan - Kardi, Kardi; Machmiyana, Ichyu; Pamurahardjo, Hemi; Sundoro, Sundoro; Adriansyah, Fery; Pratiwi, Ayu Kumala (Politeknik Penerbangan Indonesia Curug, 2023)
Aviation Security Personnel play a central role in preventing crimes within the aviation sector, bearing significant responsibilities. Strong expertise and competence are crucial in accordance with the requirements outlined in the Regulation of the Minister of Transportation of the Republic of Indonesia PM Number 28 of 2021 concerning the National Aviation Security Education and Training Program. Aviation Security Awareness training becomes essential, particularly within the Indonesian Aviation Polytechnic Curug campus environment. A 3-month Community Engagement Activity involves various partners including UPBU Budiarto, the Center for Calibration of Flight Facilities, Airnav Indonesia Budiarto-Curug Branch, and BMKG Curug. Experienced instructors in the field of Aviation Security participate in a comprehensive 2-day training, covering topics such as National Aviation Security, Criminal Technology, Trusted Insider Threats, and Aviation Security Threat Handling. The results demonstrate that several entities within the PPI Curug campus community still lack awareness in Aviation Security. The training focuses on National Aviation Security, Criminal Technology, Trusted Insider Threats, and Aviation Security Threat Handling. This training enhances the understanding and capabilities of personnel in executing aviation security measures, applying them in practice, and cultivating an overall commitment to aviation security. The ongoing Aviation Security Awareness training is expected to continuously develop the competence of aviation security personnel, enabling them to perform their duties at the required level of quality.